Apremilast in Erythema Nodosum Leprosum: A Case Series - Usha Mandloi; Neha Gogia; Durgesh Sonare; Swagat Waghmare (Wolters Kluwer Medknow Publications, 2024)
Erythema nodosum leprosum (ENL) is an immune-mediated inflammatory reaction (antigen-antibody reaction involving complement) of leprosy. Available standard treatment in the form of steroids or thalidomide does not work in all ENL patients. Apremilast is an oral phosphodiesterase-4 inhibitor with potent immunomodulatory action. At present, apremilast is approved for chronic plaque psoriasis and psoriatic arthritis, however, not in ENL. The aim of this study was to assess the effectiveness of apremilast in chronic recalcitrant ENL. It was a case series, in which apremilast was started in 10 consecutive patients with recalcitrant ENL with 10 mg morning dose with a daily increment of 10 mg until day 6, when the recommended dose of 30 mg twice daily for adults is reached. Follow-up was done every 1 month till 6 months. Three patients showed good responses. The drug was well tolerated with few side effects. The most common adverse effect reported was headache (n = 5), followed by nausea (n = 4) and diarrhea (n = 4). Apremilast has lower cost and better safety profile compared to thalidomide and may be an option with limited effectiveness for ENL.